Using observational data to emulate a randomized trial of dynamic treatment-switching strategies: an application to antiretroviral therapy. - Cain, Lauren E; Saag, Michael S; Petersen, Maya; May, Margaret T; Ingle, Suzanne M; Logan, Roger; Robins, James M; Abgrall, Sophie; Shepherd, Bryan E; Deeks, Steven G; Gill, M John; Touloumi, Giota; et al. (International journal of epidemiology, 2015)
When a clinical treatment fails or shows suboptimal results, the question of when to switch to another treatment arises. Treatment switching strategies are often dynamic because the time of switching depends on the evolution of an individual's time-varying covariates. Dynamic strategies can be directly compared in randomized trials. For example, HIV-infected individuals receiving antiretroviral therapy could be randomized to switching therapy within 90 days of HIV-1 RNA crossing above a threshold of either 400 copies/ml (tight-control strategy) or 1000 copies/ml (loose-control strategy).